Synthesis of Pd-Ag Membranes by Electroless Plating for H2 Separation. Issue 12 (December 2017) - Yaning, Li; Xinting, Kang; Huiping, Tang; Jian, Wang
Abstract: Both sequential-deposition and co-deposition based on electroless plating method for the preparation of Pd-Ag composite membranes were investigated. The morphology, phase structure, compositional homogeneity and compactness of the prepared membranes were compared. The results show that Pd-Ag membranes prepared by co-deposition are dendritic, inhomogeneous, and poorly compact, while those by multilayer sequential deposition are more homogeneous and compact. The multi-layer sequential deposition requires higher temperature and longer time for annealing to form Pd-Ag alloy. The Pd particles size is decreased by separate Ag layer and the surface of Pd-Ag membrane is smoother.